Commenting on ancient texts: interpreters and their audience in the Graeco-Roman world - Coen, S (2024)
The present study offers the first comprehensive work on papyrus commentaries in the context of ancient scholarship. Each chapter treats a different aspect of these texts. In Chapter 1 I provide the reader with a general overview of the main features of ancient commentaries in terms of content and layout, analysing a selection of examples focusing on different literary genres and comparing them to their modern counterparts. In Chapter 2 I study the material characteristics of papyrus commentaries, i.e. handwriting, use of the recto / verso, presence / absence of abbreviations, corrections, lectional and critical signs, and physical reinforcements of the papyrus. Chapter 3 takes into account the other main ‘exegetical typologies’ (treatises, marginal annotations, paraphrases, hypotheses, diegeseis), and studies in particular their similarities and differences with respect to commentaries. Finally, Chapter 4 investigates the contexts of production, use, and safekeeping of papyrus commentaries, i.e. whether they could belong to students, teachers, or scholars, and could be kept in public or private libraries and collections. This study intends to offer a better understanding of how ancient people read and studied their ‘classics’ in the light of the fundamental testimony of papyrus fragments.